2017
DOI: 10.1038/ncomms15328
|View full text |Cite
|
Sign up to set email alerts
|

An Hsp90 co-chaperone protein in yeast is functionally replaced by site-specific posttranslational modification in humans

Abstract: Heat shock protein 90 (Hsp90) is an essential eukaryotic molecular chaperone. To properly chaperone its clientele, Hsp90 proceeds through an ATP-dependent conformational cycle influenced by posttranslational modifications (PTMs) and assisted by a number of co-chaperone proteins. Although Hsp90 conformational changes in solution have been well-studied, regulation of these complex dynamics in cells remains unclear. Phosphorylation of human Hsp90α at the highly conserved tyrosine 627 has previously been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 55 publications
(92 reference statements)
4
37
0
Order By: Relevance
“…The mechanistic basis of the Sti1 dependency, or whether different Sti1dependent mutants require the same or different activities of Sti1 has not been investigated systematically. We observed that mutations that cause Sti1 dependency cluster in two regions of Hsp90, one important for interaction with Hsp70 and the other for interaction with client substrates (Genest et al 2013;Kravats et al 2017Kravats et al , 2018Zuehlke et al 2017). Suppressors of mutations in theses clusters point to separate roles for Sti1 in the two processes.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The mechanistic basis of the Sti1 dependency, or whether different Sti1dependent mutants require the same or different activities of Sti1 has not been investigated systematically. We observed that mutations that cause Sti1 dependency cluster in two regions of Hsp90, one important for interaction with Hsp70 and the other for interaction with client substrates (Genest et al 2013;Kravats et al 2017Kravats et al , 2018Zuehlke et al 2017). Suppressors of mutations in theses clusters point to separate roles for Sti1 in the two processes.…”
mentioning
confidence: 84%
“…Plasmids used are listed in Table 2. Plasmid pMR349 (Zuehlke et al 2017), which was used for most plasmid shuffle experiments, is a centromeric LEU2 plasmid with Nterminal His 6 -tagged Hsp82 under the control of the HSC82 (strong constitutive) promoter. Plasmid pMR325-K399C was used in the screen to identify suppressors of K399C Sti1 dependence (see below).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, Aha1 has a homolog, Hch1, in yeast that was lost during evolution in higher eukaryotes. Interestingly, phosphorylation of Tyr627 in hHsp90 is suspected to functionally replace Hch1 because this PTM has comparable effects on client activity as Hch1 has in yeast (Zuehlke et al 2017).…”
Section: Non-tpr-containing Cochaperonesmentioning
confidence: 99%
“…The chaperone protein Hsp90 16 is an excellent test system to investigate diverse regulation mechanisms 17 . It was recently discussed that a single PTM can functionally mimic a specific co-chaperone interaction in human Hsp90 18 . Here we take a next step and disentangle how a PTM-related point mutation, a co-chaperone interaction, and macro-molecular crowding affect the function, kinetics, and thermodynamics of this multi-domain protein.…”
Section: Figurementioning
confidence: 99%